GATE: Graduate Aptitude Test in Engineering 2024: Mathematics - Kuldeep Chaudhary; Shashank Goel; CHAUDHARY (Kuldeep); GOEL (Shashank) (Haryana G K Publications Pvt Litd, 2024)
GKP$1 (Bs Prep Series: GATE 2023: Mathematics, prepared by renowned faculty members who are subject matter experts, is your best bet to be GATE READY! The entire book has been revised and updated as per the exam syllabus. It is divided into units, chapters and further segmented into topics. The questions given with the unit have detailed answers, supported by in-depth explanations and diagrams. The book also includes well-explained sections on General Aptitude and Engineering Mathematics other than all the Mathematics. It also includes more than 2500 Objective type questions, the last two years GATE Solved papers of 2021 and 2022. Additionally, students can avail GATE previous year solved papers from 2016-2023 online from GK Publication$1 (Bs website. Features: Comprehensive theory with concepts. 2500+ MCQs & NTQs Ample questions supplemented with solutions and diagrams. Thoroughly revised and updated as per the new syllabus. 3 full-length mocks.s
Keywords: Mathematics Entrance; Competitive Examination; Gate